Precise design and preparation of two 3D organic–inorganic perovskite ferroelectrics (1, 5-diazabicyclo[3.2.2]nonane)RbX3 (X = Br, I). Issue 66 (28th July 2022) - Han, Keke; Zhang, Mengxia; Wei, Zhenhong; Ye, Xing; Rao, Wenjun; Zhang, Haina; Cai, Hu
Abstract : Two 3D organic–inorganic hybrid perovskite ferroelectrics [3.2.2-dabcn]RbX3 (X = Br for 1 ; X = I for 2 ) with Curie temperatures at 342 K and 293 K were designed and prepared by reaction of 1, 5-diazabicyclo[3.2.2]nonane with RbX. Abstract : Compared with the spherical molecule 1, 4-diazoniabicyclo[2.2.2]-octane (2.2.2-dabco), 1, 5-diazabicyclo[3.2.2]nonane (3.2.2-dabcn) bears a lower symmetry and larger size. As expected, reactions of 3.2.2-dabcn with rubidium halides gave two 3D molecular ferroelectrics [3.2.2-H2 dabcn]RbX3 (X = Br for 1 ; X = I for 2 ) with T c at 342 K (1 ) and 293 K (2 ).